2013
DOI: 10.2478/bvip-2013-0103
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterisation of Salmonella in slaughtered cattle and beef in Poland

Abstract: A total of 1229 samples, including 406 bovine hides and 406 corresponding carcasses at the slaughter level, as well as 417 beef meat from local supermarkets, were tested for the presence of Salmonella sp. Eighteen (1.5%) samples were positive for the target microorganism, and the highest prevalence (2.2%) was found in meat, followed by carcasses (1.2%) and hides (1.0%). Among the isolated strains, Salmonella enterica serotypes Enteritidis (six isolates) and Schleissheim (six strains), followed by Dublin (four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
7
2
Order By: Relevance
“…S. Abony was detected with 6.2% frequency in Mediterranean turtle Testudo graeca faeces (Briones et al 2004 ) and it was occasionally associated with human salmonellosis (Hall and Rowe 1992 ; Woodward et al 1997 ). S. Schleissheim was identified in cattle (Wieczorek and Osek 2013 ) and mistle thrush Turdus viscivorus (Hernandez et al 2003 ). Human salmonellosis caused by this serovar has been previously reported in Turkey (Aksoycan et al 1983 ) and Poland (PZH and GIS 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…S. Abony was detected with 6.2% frequency in Mediterranean turtle Testudo graeca faeces (Briones et al 2004 ) and it was occasionally associated with human salmonellosis (Hall and Rowe 1992 ; Woodward et al 1997 ). S. Schleissheim was identified in cattle (Wieczorek and Osek 2013 ) and mistle thrush Turdus viscivorus (Hernandez et al 2003 ). Human salmonellosis caused by this serovar has been previously reported in Turkey (Aksoycan et al 1983 ) and Poland (PZH and GIS 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wieczorek and Osek (24) stated that some of the S. Dublin, S. Enteritidis, and S. London strains were resistant to sulfamethizole. S. Typhimurium is resistant to multiple antibiotics (ampicillin, streptomycin, tetracycline, and sulfamethizole) (24). Rodriquez-Rivera et al (3) reported that 90 Salmonella strains (23.6%) out of 381 from subclinically infected dairy cattle and environmental samples were resistant to antibiotics varying from 1 and 11.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies were carried out to isolate and serotype Salmonella from dairy cattle and calves (4,7,14,18,21,22,24). Several researchers (4,7,14,18,21,22,24) Fecal Salmonella studies in Turkey are usually based on slaughterhouse samples or case-based notices. Gökçen et al (26) isolated S. Typhimurium from the small bowel contents of only one cow out of 298 cattle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations